Akuntabilitas Pelayanan Izin Mendirikan Bangunan (IMB) Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Di Kabupaten Tanjung Jabung Timur - Endang Meiliani; Sopian Sopian (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2020)
This research uses a qualitative method or approach. Data collection techniques are done by directobservation (observation) in the field, interviews, and documentation. Accountability in providing servicesis seen from four (4) indicators, namely: indicators of compliance with procedures, indicators of theexistence of low-cost public services, indicators of compliance with time standards, and indicators ofpublic service. The implementation of the one stop service system at the Investment Of ice and the OneStop Integrated Service (DPMPTSP) of Tanjung Jabung Timur Regency is the latest innovation as asignificant step in realizing the improvement of the quality of licensing and non-licensing services that areexpected to simplify procedures, cut time and costs required to administer a service in this case BuildingPermit (IMB). The purpose of this research is basically that the organization has run well, easily andquickly. Because with the one-door system (OSS), all services can be carried out within a period ofapproximately 1-2 weeks. Accountability for building permit services (IMB) of the investment service andone-stop integrated service (DPMPTSP) in Tanjung Jabung Timur Regency can be categorized as beingable to support accountability in the district.